A Contemporary History of Exclusion The Roma Issue in Hungary from 1945 to 2015 - Majtényi, György (Central European University Press, 2016)
This study presents the changing situation of the Roma in the second half of the twentieth century. The authors examine the effects of the policies of the Hungarian state towards minorities by analyzing legal regulations, policy documents, archival sources and sociological surveys. The book offers theoretical background to one of the most burning issues in east Europe. In the first phase (1945-61), the authors show the efforts of forced assimilation by the communist state. The second phase (1961-89) began with the party resolution denying nationality status to the Roma. The prevailing thought was that Gypsy culture was a culture of poverty that must be eliminated. Forced assimilation through labor activities continued. In the 1970s Roma intellectuals began an emancipatory movement, and its legacy can still be felt. The third phase (1989-2010) brought about some freedoms and rights for the Roma, with large sums spent on various Roma-related programs. Despite these efforts, the situation on the ground did not improve. Segregation and marginalization continues, and is rampant.